Delivery of ligands from sorting endosomes to late endosomes occurs by maturation of sorting endosomes (The Rockefeller University Press, 1992)
After endocytosis, lysosomally targeted ligands pass through a series of endosomal compartments. The endocytic apparatus that accomplishes this passage may be considered to take one of two forms: (a) a system in which lysosomally targeted ligands pass through preexisting, long- lived early sorting endosomes and are then selectively transported to long-lived late endosomes in carrier vesicles, or (b) a system in which lysosomally targeted ligands are delivered to early sorting endosomes which themselves mature into late endosomes. We have previously shown that sorting endosomes in CHO cells fuse with newly formed endocytic vesicles (Dunn, K. W., T. E. McGraw, and F. R. Maxfield. 1989. J. Cell Biol. 109:3303-3314) and that previously endocytosed ligands lose their accessibility to fusion with a half-time of approximately 8 min (Salzman, N. H., and F. R. Maxfield. 1989. J. Cell Biol. 109:2097- 2104). Here we have studied the properties of individual endosomes by digital image analysis to distinguish between the two mechanisms for entry of ligands into late endosomes. We incubated TRVb-1 cells (derived from CHO cells) with diO-LDL followed, after a variable chase, by diI-LDL, and measured the diO content of diI-containing endosomes. As the chase period was lengthened, an increasing percentage of the endosomes containing diO-LDL from the initial incubation had no detectable diI-LDL from the second incubation, but those endosomes that contained both probes showed no decrease in the amount of diO-LDL per endosomes. These results indicate that (a) a pulse of fluorescent LDL is retained by individual sorting endosomes, and (b) with time sorting endosomes lose the ability to fuse with primary endocytic vesicles. These data are inconsistent with a preexisting compartment model which predicts that the concentration of ligand in sorting endosomes will decline during a chase interval, but that the ability of the stable sorting endosome to receive newly endocytosed ligands will remain high. These data are consistent with a maturation mechanism in which the sorting endosome retains and accumulates lysosomally directed ligands until it loses its ability to fuse with newly formed endocytic vesicles and matures into a late endosome. We also find that, as expected according to the maturation model, new sorting endosomes are increasingly labeled during the chase period indicating that new sorting endosomes are continuously formed to replace those that have matured into late endosomes.(ABSTRACT TRUNCATED AT 400 WORDS)